TRAINING WILLINGNESS AND CONSTRAINTS PERCEIVED BY POULTRY FARMERS IN UTTAR PRADESH - Pratap, Jitendra; Sagar, MP; Chander, Mahesh; Chaturvedani, AK (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was conducted with the objective to evaluate the training willingness and various constraints perceived by poultry farmers in Barabanki district of Uttar Pradesh. Out of 15 blocks in Barabanki district, five blocks were selected, purposively, based on poultry population and maximum number of farms. The data were recorded from 75 respondents through the pre-tested structured interview schedule. Off–campus type of training was most preferred by 68 per cent, followed by on–campus. The majority of poultry farmers (74.7%) were chosen own village as “most preferred” venue for training. Among those who perceived constraints in receiving training 72.88 per cent perceived that family obligations do not permit to participate in training